2005
DOI: 10.1037/0012-1649.41.5.711
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine Exposure Is Associated With Subtle Compromises of Infants' and Mothers' Social-Emotional Behavior and Dyadic Features of Their Interaction in the Face-to-Face Still-Face Paradigm.

Abstract: Prenatal cocaine and opiate exposure are thought to subtly compromise social and emotional development. The authors observed a large sample of 236 cocaine-exposed and 459 nonexposed infants (49 were opiate exposed and 646 nonexposed) with their mothers in the face-to-face still-face paradigm. Infant and maternal behaviors were microanalytically coded. No opiate-exposure effects were detected. However, mothers of cocaine-exposed infants showed more negative engagement than other mothers. The cocaine-exposed dya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
124
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(141 citation statements)
references
References 48 publications
14
124
0
2
Order By: Relevance
“…Co-occurrences, or the affective match between parent and child, was examined using three conditional probabilities: parent in positive arousal given child in positive arousal, parent in neutral arousal given child in neutral arousal, and parent in negative/ withdrawn arousal given child in negative/withdrawn arousal. These probabilities assess the proportion of time out of the entire interaction when parent and child matched on level of arousal, consistent with previous research (Tronick et al, 2005).2. Sequential relations.…”
supporting
confidence: 67%
See 3 more Smart Citations
“…Co-occurrences, or the affective match between parent and child, was examined using three conditional probabilities: parent in positive arousal given child in positive arousal, parent in neutral arousal given child in neutral arousal, and parent in negative/ withdrawn arousal given child in negative/withdrawn arousal. These probabilities assess the proportion of time out of the entire interaction when parent and child matched on level of arousal, consistent with previous research (Tronick et al, 2005).2. Sequential relations.…”
supporting
confidence: 67%
“…The fourth composite addressed periods in which the infant looked at the parent's face (sum of social attend and social play) and was termed social orientation. The monadic phases system has been used extensively in research on parent-infant affective matching in healthy and high-risk populations (Cohn & Tronick, 1988;Feldman, 2003;Feldman et al, 1999;Field et al, 1990;Lester et al, 1985;Tronick et al, 2005;Weinberg et al, 1999).…”
Section: Coding Infancymentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, well-controlled studies have demonstrated that prenatal cocaine exposure does in fact affect fetal physical growth, and results in an increase of premature birth, and generalized growth retardationincluding decreased birth weight, shorter body length, and smaller head circumference (Bigsby et al, 2011;Covington et al, 2002;Gouin et al, 2011;Mayes et al, 2003). Abnormal infant behavioral outcomes have also been documented; these outcomes include abnormalities related to lower arousal, poorer quality of movement and self-regulation, higher excitability, jitteriness, and more non-optimal reflexes (Lester et al, 2002;Richardson et al, 2008;Singer et al, 2000;Tronick et al, 2005). Studies have revealed that the behavioral outcomes observed at birth continue and sometimes worsen after 12 months of age (Bigsby et al, 2011;Chiriboga et al, 2007;Mayes et al, 2003;Richardson et al, 2008).…”
Section: Cocainementioning
confidence: 99%